Safety and Potential Side Effects of ß2-Agonists: A Still Debated Question - Bozzola, Elena; Bozzola, Mauro; Barberi, Salvatore; Cutrera, Renato; Villani, Alberto (International Journal of Pediatrics and Child Health, 2013)
In the last years, the safety profile of ß2-agonists has been largely discussed as there are concerns about the adverse effects of their regular use. In this review, we analyze the main questions relating both morbidity and mortality of currently available ß2-agonists. Although questions still remain regarding the issue of safety, evidence from epidemiological studies is strongly suggestive that the use of ß2-agonists is not dangerous.